Designing a quality scorecard (QSC) for system integration in the era of Industry 4.0. Issue 2 (31st January 2022) - Roh, Hye Young; Ali, Shujaat; Song, Hojun; Shin, Wan Seon
Abstract : Purpose: This study aims to investigate the criteria to measure and manage a software project's quality indicator elements needed to implement system integration in the Industry 4.0 era. Design/methodology/approach: The standard software process model SPICE: a crucial part of the system integration software development process, is analyzed to explore how the factors of the SPICE model rate qualitatively on the quality scorecard (QSC). QSC is a qualitative performance measurement model based on the cost of quality (COQ) perspective. The SPICE model's effectiveness is examined in terms of system integration (SI) quality, and factors for improving this quality are determined. Findings: The authors proposed future directions for improving SI management. The seven SPICE process groups were analyzed comparatively by matching them to the QSC. The SPICE model was found to achieve 63% with the required factors in QSC. Also, the uncommitted items indicated need to be considered for additional management in SI quality. Practical implications: Since SPICE is revised every five years, it is suggested from this study that diagnosing the assessment items from the COQ perspective using QSC is one strategy to quickly enhance the quality of SI management in this rapidly changing technology revolution. Originality/value: This research is the first study of its kind, proposing a methodology for adapting quickly to the Fourth Industrial Revolution's changes and showing how the standards have changed the SPICE model over time.